The Antimicrobial Activity of a Carbon Monoxide Releasing Molecule (EBOR-CORM-1) Is Shaped by Intraspecific Variation within Pseudomonas aeruginosa Populations - Lindsey Flanagan; Lindsey Flanagan; Rachel R. Steen; Karinna Saxby; Karinna Saxby; Mirre Klatter; Benjamin J. Aucott; Craig Winstanley; Ian J. S. Fairlamb; Jason M. Lynam; Alison Parkin; Ville-Petri Friman (Frontiers in Microbiology, 2018)
Carbon monoxide releasing molecules (CORMs) have been suggested as a new synthetic class of antimicrobials to treat bacterial infections. Here we utilized a novel EBOR-CORM-1 ([NEt4][MnBr2(CO)4]) capable of water-triggered CO-release, and tested its efficacy against a collection of clinical Pseudomonas aeruginosa strains that differ in infection-related virulence traits. We found that while EBOR-CORM-1 was effective in clearing planktonic and biofilm cells of P. aeruginosa strain PAO1 in a concentration dependent manner, this effect was less clear and varied considerably between different P. aeruginosa cystic fibrosis (CF) lung isolates. While a reduction in cell growth was observed after 8 h of CORM application, either no effect or even a slight increase in cell densities and the amount of biofilm was observed after 24 h. This variation could be partly explained by differences in bacterial virulence traits: while CF isolates showed attenuated in vivo virulence and growth compared to strain PAO1, they formed much more biofilm, which could have potentially protected them from the CORM. Even though no clear therapeutic benefits against a subset of isolates was observed in an in vivo wax moth acute infection model, EBOR-CORM-1 was more efficient at reducing the growth of CF isolate co-culture populations harboring intraspecific variation, in comparison with efficacy against more uniform single isolate culture populations. Together these results suggest that CORMs could be effective at controlling genetically diverse P. aeruginosa populations typical for natural chronic CF infections and that the potential benefits of some antibiotics might not be observed if tested only against clonal bacterial populations.